Battery performance characterisation for stand-alone photovoltaic systems - Purcell, C J de V (Energy Research Centre, 2016)
One of the main factors limiting optimisation of PV system designs over the life of the system has been the lack of battery test data appropriate to PV applications. The main objective of this study was to determine accurate empirical data for locally available lead-acid batteries which could be used in photovoltaic systems and to present this data in a format directly applicable to PV system designers. The study included (i) a review of battery performance regimes typical of PV systems; (ii) a literature review of lead-acid battery performance and reactions important to PV applications, battery electrical models, battery life models, a review of specialist PV battery designs and the interaction of battery and voltage regulator in PV systems;. (iii) a review of testing and research literature, and the design of a suite of experimental procedures suitable for characterising batteries under PV operating regimes; (iv) the design and construction of a specialised battery test-unit to automatically perform tests and capture data; (v) selection, testing and characterisation of five generic types of batteries which could be used in local PV applications. The five types of lead-acid battery were: 1) conventional calcium alloy positive and negative grids, flat plate, flooded electrolyte, vented casing; 2) low antimony alloy positive grid, conventional calcium negative grid, flat plate, flooded electrolyte, vented casing; 3) low antimony alloy positive grid, heat treated calcium negative grid, flat plate, immobilised absorbed electrolyte, sealed casing with 0 2 cycle gas recombination; 4) antimony alloy positive and negative grids, flat plate, flooded electrolyte, vented casing; 5) antimony alloy positive and negative grids, tubular plate, flooded electrolyte, vented casing. Selenium grid alloy cells and gelled electrolyte batteries were not represented amongst the batteries tested, owing to problems of availability or cost.